Analisis Kandungan Informasi Stock Split dan Likuiditas Saham: Studi Empiris Pada Non-synchronous Trading - Indah Kurniawati (The Indonesian Journal of Accounting Research, 2013)
Stock Split has been a debatable and puzzling phenomenon for financial theoritist, for there is inconsistency between the theory and practice. Theoretically, Stock Split will only increase the amount of shared stocks, without increasing the profit for investors, nor adding any economic value to the firms. While in practice, some empirical evidences show that market tends to react to the announcement of Stock Split.The objective of this research is to empirically examine about the information content of Stock Split and its influence to stock liquidity by firstly corecting the beta bias, since the trade condition in Jakarta Stock Exchange is still a non-synchronous trading. Sample consists of 61 stocks performing the Stock Split during the period of June 1994 to June 1997.The examination of information content of Stock Split made use of Single Index Model (William Sharpe, 1963) and correcting the beta bias made use of Fowler and Rorke Method (1983) with four lags and four leads (Hartono & Surianto,1999) Comparison of stock liquidity before and after performing the Stock Split made use of paired sample test.The result of this research shows that Stock Split has information content which is negatively responded statistically but significantly responded by the market around the date of Stock Split announcement. The difference between stock liquidity before and after the Stock Split is insignificant.